Report of the Working Group on Major and Medium Irrigation Programme for the Eighth Plan (1990-95) - Planning Commission (Planning Commission, 1989)
The irrigation potential that can be ultimately achieved through major and medium irrigation projects in each State should be re-assessed by the State Governments. the assessment should be made project-wise, 1. e. projects completed, ongoing and yet to be taken up.
Government of India
Government of India